RETRACTED: MicroRNA-326 Functions as a Tumor Suppressor in Breast Cancer by Targeting ErbB/PI3K Signaling Pathway - Ghaemi, Zahra; Soltani, Bahram Mohammad; Mowla, Seyed Javad (Frontiers in Oncology, 2019)
Breast cancer represents the most common malignancy in women worldwide and the ErbB/PI3K pathway has been found to play a crucial role in regulation of the cancer cell growth. MicroRNAs have been implicated in regulating diverse cellular pathways and therefore, understanding the link between the regulatory microRNAs and the ErbB/PI3K signaling pathway could potentially be helpful for breast cancer prevention and treatment. The aim of this study is to examine the regulatory effect of miR-326 on ErbB/PI3K signaling pathway in breast cancer development and progression. The results of qRT-PCR, RNA seq, and array data indicated that miR-326 was remarkably down-regulated in breast tumor tissues and correlated with poor survival outcome. Importantly, very low levels of miR-326 expression were found in aggressive breast cells compared to less-aggressive cell types. Mechanistically, a gene network including EGFR, ErbB2, ErbB3, AKT1, AKT2, and AKT3 targeted by miR-326, thereby providing suppression of ErbB/PI3K pathway, detected by RT-qPCR, and dual luciferase assay. In addition, Western blot analysis revealed that miR-326 upregulation decreased PI3K signaling activity by decreasing total AKT and p-AKT protein level in SKBR3 cell lines. Interestingly, up regulation of ErbB2 rescued the effect of miR-326 on miR-326 target genes. Further functional assays demonstrated that up regulation of miR-326 significantly suppressed cell growth as evidenced by cell cycle, cell cycle associated genes expression, colony formation and MTT assays and induced apoptosis, detected by Annexin V-PI. In addition, EMT markers RT-qPCR, scratch, and Transwell assays showed inhibited cellular migration and invasion following miR-326 upregulation. Altogether, our results revealed that miR-326 play a tumor-suppressive role in breast cancer through inhibiting ErbB/PI3K pathway and miR-326 may serve as a potential therapeutic target for the treatment of patients with breast cancer.